Modelling the macroeconomic impact of HIV/AIDS in the English Speaking Caribbean - Nicholls, S....[et al] (2000)
Examines the impact of the epidemic on key macroeconomic indicators. Estimates the costs of the disease and provides a methodology through which the cost implications can be readily generated as information on the number of persons affected is updated.